(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
This article explores automation methodologies directed at devising optimal configurations for train operations. The investigation emphasizes the crucial incorporation of cutting-edge technologies to augment operational efficiency, mitigate costs, and streamline decision-making processes within the dynamic domain of railway systems. By undertaking an exhaustive examination of prevailing literature, this article aspires to furnish a comprehensive survey of contemporary methodologies, challenges, and prospects associated with the automation of train operation configurations.